The reality of Educational Media in secondary education schools in the city of Riyadh - Alanazi, Hanan Mamdouh (Journal of Educational and Psychological Sciences, 2020)
The purpose of this research is to reveal the reality of media education in secondary education schools in Riyadh, from the teachers' point of view. To achieve the aims of the research, descriptive design and the questionnaire were used as a tool for research. It was distributed to a random sample of (30) female high school teachers was distributed in the city of Riyadh in the academic year 1440- 1441 AH. The results of the research showed: Obtaining the reality of media education in secondary education schools in the city of Riyadh at a total average of (2.77 out 3), With a degree (large), and at the level of fields; the field of the importance of teaching media education got the highest overall average of (2.85), followed by the field of obstacles to applying media education with an average of (2.78), and finally the field of media education concept with an average (2,67) All of them are (large), According to the results, proposals and Recommendations were presented to remove obstacles and awareness of the importance of teaching media education.
Keywords: Reality; Media Education; High School; Riyadh